The management and implementation of zurri waqf in Malaysian waqf instituition - Sri Wahyu Sakina Ahmad Sanusi; Mohd Fairuz Md Salleh; Salmy Edawati Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2023)
In accordance with Islamic sharia, zurri waqf (family waqf) has been used as an instrument for estate planning and family inheritance. The issue of abandoned property management has yet to be fully resolved, and zurri waqf is one option for the estate distribution. In Malaysia, the State Religious Council is the administrator of zurri waqf practices. The implementation, on the other hand, is minimal and not proactive. Hence, the objective of this study is to identify the practice of zurri waqf implementation in Malaysia. This study employs a qualitative interview method with eight respondents. This study discovered that the practice of zurri waqf implementation is at a passive level, but the improvements can still be made. For instance, the rectification in the management procedures can be done as zurri waqf assets have the potential for economy development and ongoing benefit to the family and society in general. The findings of this study in terms of restructuring the existing procedures according with the experts’ suggestion such as lineage restrictions on beneficiaries and appointment of zurri waqf consultants may aid in the proactive implementation of zurri waqf as well as the preservation of Muslims' equity in strengthening the economic stability of the family and society in general.